KINERJA KOMISI PEMILIHAN UMUM DAERAH DALAM PENYELENGGARAAN PEMILIHAN KEPALA DAERAH KABUPATEN KUANTAN SINGINGI TAHUN 2011 - ", Zulhendrika; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Local election is a form of democracy in the region in choosing the head area that is set in the law number 22 of 2007, and it is an embodiment of people’s sovereignty. Election practice is usually characterized by the appearance of some problems as in the district of Kuantan Singingi was held on 7 April 2011. There were some problems happened in this research such as the lack of coordination among committee, budget, facilities and human resources, socialization election and logistics.The data in this reasearch obtained with qualitative approach of primary and secondary data. The primary data was obtained by means of a literature study in the form of archives, data, documentation, and literature. While the secondary data obtained by field studies in the form of observations and interviews with selected key informants based on elements of the election, supervisor election, participants and the public, with the aim to achieve the informations for this research. This study aims to investigate the performance of the election Commission in preparing, implementing, managing conflict and determining the constraints experienced by the election commission in the implementation of the election in Kuantan Singingi in 2011.The results showed that the election commission in Kuantan Singingi had conducted the implementation optimally in accordance with the rules applicable, but there were obstacles or problems happened that caused confusion in the election process in Kuantan Singingi regency in 2011.Keywords: The Performance, Local Elections, Regional Elections Commission (KPUD)